Cataract, ocular surgery, aphakia, and the chromatic expression of the painter Jovan Bijelić - Nikolić, Ljubiša Borislav; Jovanović, Vesna (Vojnosanitetski pregled, 2017)
Background/Aim. Approaching art from the standpoint of optics and the artist’s eye pathology can sometimes explain the shift of the spectral colors in the work of some artists with cataract and aphakia. This may not be obvious in the paintings of other artists with the same eye pathology. The aim of this study was to create a timeline from the recently obtained details of the cataract surgery, his best corrected aphakic visual acuity, and the last paintings of the artist Jovan Bijelić. Methods. The research included primary and secondary source material: Bijelić’s paintings from all stages of his career, interviews with Bijelić and his eye surgeon, art criticism, sources with the description of Bijelić’s symptoms, hospital archives, discussion with art historians, comparison of his palette from different periods. Results. Jovan Bijelić was nearly blind from cataract in 1957. He underwent an unsuccessful cataract surgery in 1956, followed by enucleation of the operated eye. In 1958, 20/25–20/20 vision was regained, after the extracapsular cataract extraction and sector iridectomy in his right eye, with the posterior lens capsule discision afterwards. Xanthopsia and cyanopsia are not present in his art, which is not a representation of visualized objects. Conclusion. The response of Jovan Bijelić to cataract and aphakia was predominantly a change of his style.